MODIFICATION OF CARBON PASTE WORKING ELECTRODE WITH TITANIUM(IV) OXIDE NANOPARTICLE FOR VOLTAMMETRIC ANALYSIS OF DICLOFENAC - Suzetta, Feby
Diclofenac (DCF), the common name of 2(2-6-dicloroanilino)phenyl acetic acid, is an active pharmaceutical compound, specifically a non-steroidal anti-inflammatory drug that can be toxic for aquatic organisms. One method that is used to analyse diclofenac is voltammetry. Carbon based electrodes which are often used as working elektrode in voltammetry have poor performance, thus usually modified, for example with nanoparticles, like titanium(IV) oxide (TiO2). The aim of this study is to determine the effect of modification of carbon based working electrode with TiO2 nanoparticles (TiO2-NPs) on diclofenac concentration analysis. The working electrodes used in this study were carbon paste electrode (CPE) made of graphite and paraffin oil. Modification of TiO2-NPs was done using two different methods, by dropping TiO2 suspension on the surface of CPE and by mixing the TiO2 powder with graphite and paraffin oil. The electrodes were optimized to determine the optimum TiO2-NPs/CPE composition and voltammetry technique, then validated by determining the effect of scan rates, detection limit, linear range, reproducibility, and repeatability. The voltammetry analysis result of diclofenac concentration was compared to HPLC analysis result. The cyclic voltammetry analysis of 10-4 M diclofenac solution in pH 6 phosphate buffer showed that TiO2-NPs modified CPE increase the peak current. Modification by mixing the TiO2 gave higher peak current than suspension dropping, with 8% as the optimum TiO2-NPs composition. The optimum technique is square wave voltammetry. Scan rate analysis showed that the electron transfer reaction on the electrode is an diffusion-controlled process. The optimum TiO2-NPs/CPE had great repeatability and reproducibility with respective %RSD of 6.26% (n = 20) and 1.43% (n = 3), along with the linear range of 0.5 – 90 ?? and the limit of detection of 3.74 ?M. The t-test result showed that the result of sample analysis with voltammetry using the optimum TiO2-NPs/CPE had no significant difference from HPLC analysis.